2019
DOI: 10.1093/rheumatology/kez562
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine is associated with a lower risk of polyautoimmunity: data from the RELESSER Registry

Abstract: Objectives This article estimates the frequency of polyautoimmunity and associated factors in a large retrospective cohort of patients with SLE. Methods RELESSER (Spanish Society of Rheumatology Lupus Registry) is a nationwide multicentre, hospital-based registry of SLE patients. This is a cross-sectional study. The main variable was polyautoimmunity, which was defined as the co-occurrence of SLE and another autoimmune diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 44 publications
4
25
0
1
Order By: Relevance
“…Another question is whether hydroxychloroquine (HCQ) can be used in patients with pSS and MG. HCQ is an essential drug for patients with CTDs including SLE and SS, but special caution should be taken when used in MG patients. Although data from the Spanish society of Rheumatology Lupus Registry showed that HCQ protected against polyautoimmunity for patients with SLE ( 38 ), Varan et al reported a case of SLE in which MG developed with the use of HCQ, and regressed with its withdrawal ( 39 ). In a series of 17 patients with SLE and MG, Jallouli et al found that eight patients (47%) developed MG after initiation of HCQ, but only one patient who received HCQ had an exacerbation of myasthenic symptoms ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another question is whether hydroxychloroquine (HCQ) can be used in patients with pSS and MG. HCQ is an essential drug for patients with CTDs including SLE and SS, but special caution should be taken when used in MG patients. Although data from the Spanish society of Rheumatology Lupus Registry showed that HCQ protected against polyautoimmunity for patients with SLE ( 38 ), Varan et al reported a case of SLE in which MG developed with the use of HCQ, and regressed with its withdrawal ( 39 ). In a series of 17 patients with SLE and MG, Jallouli et al found that eight patients (47%) developed MG after initiation of HCQ, but only one patient who received HCQ had an exacerbation of myasthenic symptoms ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCQ has proved invaluable in the management of skin manifestations of SLE as well as other immunological-related skin disorders 16 . There are more wide-reaching effects of HCQ with a recent study reporting attenuation of polyautoimmunity in patients with SLE 17 . In a nationwide Spanish study of 3679 SLE patients with 13.6% having polyautoimmunity (comorbid autoimmune thyroiditis, RA, scleroderma, inflammatory myopathy, and mixed connective tissue disease), antimalarial drugs were associated with a lower risk of polyautoimmunity (OR 0.50, 95% CI 0.38-0.67) 17 .…”
Section: Antimalarials As a Rheumatic Disease Treatmentmentioning
confidence: 99%
“…There are more wide-reaching effects of HCQ with a recent study reporting attenuation of polyautoimmunity in patients with SLE 17 . In a nationwide Spanish study of 3679 SLE patients with 13.6% having polyautoimmunity (comorbid autoimmune thyroiditis, RA, scleroderma, inflammatory myopathy, and mixed connective tissue disease), antimalarial drugs were associated with a lower risk of polyautoimmunity (OR 0.50, 95% CI 0.38-0.67) 17 . An important advantage of HCQ is safety in pregnancy, first reported by Buchanan and colleagues in the United Kingdom in 1992 18 .…”
Section: Antimalarials As a Rheumatic Disease Treatmentmentioning
confidence: 99%
“…During SLE and primary APS, HCQ administration decreases levels of type I IFN in patients' serum, and expression of type I interferon (IFN)-inducible genes in peripheral blood mononuclear cells ( 62 ). In a retrospective cohort of 3,679 Spanish SLE patients, HCQ treatment conferred an odds ratio of 0.5 for polyautoimmunity ( 63 ). Healthcare registry data for 220 million individuals showed that HCQ intake was associated with a lower risk for coronary artery disease ( 64 ).…”
Section: Mechanisms Of Cq/hcq-induced Immune Modulationmentioning
confidence: 99%